Constructing Emotional and Relational Understanding: The Role of Mother–Child Reminiscing about Negatively Valenced Events. Issue 2 (2nd April 2013) - Laible, Deborah; Panfile Murphy, Tia; Augustine, Mairin
Abstract: Although there is some evidence from cross‐sectional studies that reminiscing is an important context in which children construct socioemotional understanding, longitudinal evidence is lacking. The goal of this study was to examine longitudinally the links between the quality of reminiscing at 42 months and children's subsequent socioemotional development at 48 months. At 42 months, mothers and children reminisced about a past negatively‐valenced emotional event. These conversations were coded for maternal elaboration, the children's contribution and engagement, and the degree to which meaning was co‐constructed by the dyad. At 42 and 48 months, children took part in laboratory measures of socioemotional development. Whereas there were few links between concurrent reminiscing quality and sociomoral development, aspects of reminiscing quality at 42 months (including children's engagement and the dyad's co‐construction of meaning) were related to children's emotional understanding, empathy, representations of relationships, and moral‐self at 48 months. This study provides some of the first longitudinal evidence that reminiscing conversations are linked with children's subsequent sociomoral understanding.